Evaluation of Antithyroid Antibodies in Polycystic Ovarian Syndrome of Reproductive Women - Akhter, Salma; Tasnim, Nayeema; Islam, Mohammed Hafizul; Akter, Pervin; Karmakar, Pijush; Salma, Ummey (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Polycystic Ovarian Syndrome (PCOS) is common but a treatable cause of infertility in reproductive women. Thyroid hormone abnormality is commonly seen in Polycystic Ovarian Syndrome of reproductive women. Antithyroid antibodies have been detected in women with PCOS. The aim of the present study is to evaluate the antithyroid antibodies in Polycystic Ovarian Syndrome (PCOS) of reproductive women. Materials and methods: A hospital based cross-sectional comparative study was conducted in the outpatient Department of Obstetrics and Gynaecology in CMCH, Institute of Nuclear Medicine and Allied Subject and the Department of Biochemistry in CMC. Eighty (80) PCOS women diagnosed by ultrasonography were taken by nonprobability convenient sampling, considered as group A and another twenty (20) healthy women were taken, considered as group B. Important variables in this study were serum anti-TPO antibody, anti-Tg antibody, TSH, age, menstrual history, hirsutism, waist circumference and BMI. Results: This study revealed a statistically significant higher prevalence of autoimmune thyroiditis in PCOS cases in comparison to healthy group (32.5 % and 37.5% patients had increased anti-TPO and anti-Tg antibodies respectively). Mean serum anti-TPO and anti-Tg antibodies were increased significantly in PCOS cases than that of healthy women group. Mean serum TSH was not increased significantly in PCOS cases than that of healthy group.52.5%, 47.5% patients had oligomenorrhea and amenorrhea respectively, 21.2% had hirsutism, 68.8% cases were overweight & obese and 77.5% were central obese. Conclusion: High prevalence of thyroid autoimmunity in euthyroid PCOS patients refers to the importance of screening not only thyroid hormone levels but also thyroid antibody level during the investigation of PCOS of reproductive women and thereby early diagnosis and management of infertility associated with PCOS. JCMCTA 2021 ; 32 (2) : 105-110